Corporate Social Responsibility Accountability through Hamka’s Tasawuf Lens - Dhina Mustika Sari (Yayasan Rumah Peneleh, 2021)
Each entity has the responsibility to contribute in developing the community through a Corporate Social Responsibility (CSR) program. However, the implementation of CSR in modern accounting practices does not always emphasize philanthropy value, instead it still hinges on a capitalistic orientation to maximize profit. The aim of this article is to deconstruct the concept of CSR accountability, which has so far been controlled by capitalistic values. Hamka's Tasawuf thought with the core of tawhid was employed as methodology, which was then complemented by self-awareness as a servant, and refers to an ideology in which one believes that integration of nature, life, and human. This can become the rationale for the construction of social responsibility. Akhlaqy concept on accountability involves religiosity and self-sincerity in implementing CSR. This way, CSR accountability can be directed towards God, as the Giver of Life.